TRADISI MANDHASIYA DESA PANCOT DAN POTENSINYA SEBAGAI DAYA TARIK WISATA KABUPATEN KARANGANYAR - Murdyaningsih, Devi (El Tarikh : Journal of History, Culture and Islamic Civilization, 2021)
AbstractThe Mandhasiya tradition is a village clean tradition carried out by the people of Pancot Village, Tawangmangu District, Karanganyar Regency. This tradition has an important role in the realization of social cohesion between communities. The purpose of this study is to explain the identity and history of Pancot Village, to describe the procession of implementing the Mandhasiya tradition, and to provide an overview of the attractiveness of cultural tourism. The method of this research used a descriptive qualitative method. The data of this research was obtained through literature study and in-depth interview. Data analysis was performed by data reduction and data presentation. The results showed that the history of Pancot Village originated from the story of the defeat of Prabu Baka by Putut Tetuka. This tradition is carried out every seven months on Tuesday Kliwon wuku Mandhasiya. The procession of implementing the Mandhasiya tradition has two stages, namely the pre-ceremony and the implementation of the ceremony. The attractiveness of this traditional tourism lies in the aspects of attractions, amenities, accessibility and activities. Based on the SWOT analysis, this tradition deserves to be used as one of the cultural tourism objects in Karanganyar Regency.Keywords: Mandhasiya Tradition, Pancot Village, Tourist Attraction